The prognostic significance of bone marrow involvement in diffuse large B cell lymphoma according to the flow cytometry. Issue 10 (24th August 2019) - Greenbaum, Uri; Levi, Itai; Madmoni, Odelia; Lior, Yotam; Al-Athamen, Kayed; Perry, Zvi Howard; Hatzkelzon, Lev; Shubinsky, George
Abstract: The significance of minimal bone marrow (BM) involvement in diffuse large B cell lymphoma (DLBCL), as determined by flow cytometry (FC), is unclear. Patient outcomes were retrospectively analyzed based on their BM biopsy and FC involvement. Eighty-one patients were included, 21 and 51 were positive for biopsy(B+) and FC(FC+) respectively. B+ FC+ patients had a 52.3%CR rate, the B− FC+ group had 76.7%, and the B− FC− had 73.3%. Mean time to progression (TTP) was 67.45, 76.8, and 79.3 months and median overall survival (OS) was 54.4, 76.6 and 69.5 months for the B+ FC+, B− FC+, and B− FC− groups respectively. A cutoff of 1% pathologic cells was an independent risk factor for TTP. In a multivariable analysis including International Prognostic Index (IPI), sex and HB, FC+ was independently associated with TTP (but not OS) at 5 years (HR 2.64, 95%CI 1.03–6.77) and at 7 years(HR 2.83, 95%CI 1.08–7.39). In summary, FC determined minimal involvement may suggest an intermediate risk group of DLBCL patients.